Control system design for supply air temperature (SAT) in AHU - Liew, Chong Kit (2018)
Air Handling Unit can be found in several types of building. Recently, research activities had shown concern on energy consumption. And it has discovered that cooling load of a building consumed a high percentage of energy compare with the total energy consumption. Thus, reducing of the total energy consumption becomes an interesting topic. One of the way to achieve this goal is by controlling the chilled water valve using an optimal PID controller. There are several methods to design the PID, in this project, model of the control system for chilled water valve, it uses one of the method in empirical method, two-point method. The PID controller design used 3 types of methods, such as Z-N tuning method, IMC method, and GPM method for the calculation of PID. The result of the experimental is done by using a simulation, LabVIEW. All the method used able to meet the desired setpoint, however the stability of each method was very different and varies a lot. Therefore, choosing a more stability controller parameter will be wise choice. Future improvement of the experiment can be done on the actual system itself, controlling temperature of the chilled water.